Dimeters in L_2 classes of differentiated functions determined by continuity moduli of higher orders - Shalaev , V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Sharp inequalities are obtained in the space L_2, connecting the best approximations of differentiable 2π-periodic functions by trigonometric polynomials with integrals containing the higher-order moduli of continuity of the derivatives of these functions. The Kolmogorov widths of certain classes of functions, defined by these moduli of continuity, are computed.